Transmitting the TurÄth: A Portrait of Islamic Tradition in the North Coast of Java in Countering Radicalism - Irfan, Agus; Makhsun, Toha; Mujib, Ahmad; Madrah, Muna Yastuti (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2020)
This article discusses one of the important Islamic traditions in the coastal areas of Central Java, Indonesia, where the majority of Muslims receive moral teachings through the recitation of turÄth from the local islamic clerics, known as Kiai. This form of Islamic tradition is represented by Pengajian Ahad Pagi in Semarang and Jamaah Muji Nabi (often abbreviated as Jamuna) in Demak Regency. Examining religious movements through a phenomenological approach, this study found that in delivering the religious materials both Pengajian Ahad Pagi and Jamaah Muji Nabi use the transmission method. Such an approach emphasizes the aspect of narration, in which the Kiai reads one of the turÄth (classical Islamic books), interprets it word by word, and then explains it comprehensively. Besides, the educational style delivered by the Kiai in the two said turÄth-based teachings emphasized the aspect of Sufism that involved sense. It stands to reason that the congregation feels motivated, both in terms of religious knowledge and morals, and is possibly not trapped in a binary mindset seeing religious issues in black and white as framed by the radical groups. The findings of this study indicate that Pengajian Ahad Pagi and Jamaah Muji Nabi found the continuity of their vision and initial idea in response to the culture and life of the surrounding community.